YUMEYA RESTAURANT’S MARKETING STRATEGY POST-EMERGENCY RESTRICTIONS TOWARDS COMMUNITY ACTIVITIES (PPKM) DUE TO THE COVID-19 CASE’S NUMBER’S INCREASE - Shanty Syarifah; Sa’diyah El-Adawiyah (International Journal Labs, 2022)
PPKM indirectly affects the continuity of the business world. Similarly, the restaurant business sector, is what makes restaurant entrepreneurs have to think hard about how to bounce back their business. Yumeya Restaurant was able to get through the crisis period after being hit by the emergency PPKM period with his activities in the field of marketing communication. Marketing communication became one of the tools that Yumeya Restaurant did to bounce back. Therefore, this research activity aims to find out the marketing communication strategy of Yumeya Restoran to rise due to emergency PPKM rules due to increased Covid 19 cases. The research method uses a qualitative approach by conducting research and analysis of the phenomenon of marketing communication at Yumeya Restaurant post-PPKM Emergency. The data collection techniques carried out are interviews and observations with sources. The informant in this study involved 1 (one) person as a key informant people as supporting informants. The results revealed that the marketing Communication Strategy conducted by Yumeya Restaurant by utilizing 4 elements of the marketing mix and elements of the marketing communication mix, namely advertising, sales promotion, special events and experiences, public relations and news, direct marketing, and personal sales. To market its products Yumeya Restaurant uses marketing communication strategies in a persuasive, informative, and educative way.